P0901REAL-WORLD ASSESSMENT: CLINICAL EFFECTIVENESS AND SAFETY OF VITAMIN D THERAPIES IN ND-CKD PATIENTS. (6th June 2020) - Germain, Michael J; Paul, Subir K; Broumand, Varshasb; Fadda, George; Nguyen, Andy; McGarvey, November; Gitlin, Matthew; Ashfaq, Akhtar
Abstract: Background and Aims: Extended-release calcifediol (ERC), active vitamin D analogs (VDA), and nutritional vitamin D (NVD) are the predominant vitamin D therapies (VDTs) commonly used for treatment (Tx) of secondary hyperparathyroidism (SHPT) in adults with stage 3 or 4 non-dialysis chronic kidney disease (ND-CKD) and vitamin D insufficiency (VDI). Clinical trials have demonstrated varying efficacy on serum total 25-hydroxyvitamin D (25D) and intact parathyroid hormone (iPTH) across VDTs. This study aimed to descriptively assess the real-world experience of various VDTs in increasing 25D, reducing iPTH, and modifying serum calcium (Ca). Method: Medical records of the first 376 adult patients with stage 3 or 4 CKD and a history of SHPT and VDI who met study criteria from 18 geographically representative United States nephrology clinics were reviewed from 1 year before through 1 year after initiation of VDT. Key study variables included patient demographics, medication usage, and laboratory results. The study population had a mean age of 69.5 years with gender and racial distributions representative of the US ND-CKD population. Patients were stratified into cohorts based on their index therapy at index date: ERC (n=174), VDA (n=55) and NVD (n=147). Results: Patients treated with NVD were predominantly CKD Stage 3 (69.4%), while CKD Stage 4 were the majority of those treated with ERC (53.4%) and VDA (61.8%). The ERC Tx'ed subjects demonstrated an increase in 25D by 23.7 ± 1.6 ng/mL (p<0.001) and a decrease iPTH by 35 ± 6.2 pg/mL (p<0.001) without statistically significant impact on serum calcium (Ca) and phosphorus (P) levels. The VDA Tx'ed group demonstrated an increase in 25D by 5.5 ± 1.3 ng/mL (p<0.001) without statistically significant impact on iPTH and serum phosphorus levels. Additionally, serum Ca increased by 0.2 ± 0.1 pg/mL (p<0.001) among VDA recipients. The NVD Tx'ed group demonstrated an increase in 25D by 9.7 ± 1.6 ng/mL (p<0.001) without statistically significant impact on iPTH and serum Ca and P levels (Table 1). Conclusion: Clinical effectiveness and safety varied across VDTs. ERC was the only VDT which significantly reduced mean iPTH in the real world setting despite highest mean levels at baseline among the three cohorts. Additionally, subjects treated with ERC demonstrated the largest mean increase in 25D and ERC was the only VDT which raised mean 25D to the normal range (> 30 ng/mL). Patients treated with ERC and NVD saw no statistically significant impact on serum Ca and P levels; however, those treated with VDAs saw a small, but statistically significant increase in serum Ca levels.